Perception and Attitude of the Society Bangka Belitung Province Towards the Development of Halal Tourism - Wulpiah, Wulpiah; Meilani, Reka (Universitas Bangka Belitung, 2025)
Tourism is a sector that plays a significant role in improving a country's economic development. There are desires the development of the tourism sector is expected to encourage efforts to improve the welfare of local communities through the provision of employment opportunities. Likewise, halal tourism has now begun to trend not only in Indonesia, but is one of the core products for various Muslim-majority countries. This research is urgently carried out, so that the people of Bangka Belitung Province have a moderate perception and in the future tourist destinations such as culinary tourism, natural tourism, educational tourism and religious tourism can become icons and if they have a